The unquiet western front: Britain's role in literature and history - Bond, Brian (Cambridge University, 2013)
Britain's role in the First World War has been portrayed mainly through literature, films and plays, in most cases with a marked un-historical, anti-war spirit. This book follows the controversy from 1918 to the present, and concludes that historians are finally permitting the War to be placed in proper perspective.